2014
DOI: 10.1055/s-0034-1368590
|View full text |Cite
|
Sign up to set email alerts
|

Natural Products as Potential Human Ether-A-Go-Go-Related Gene Channel Inhibitors – Screening of Plant-Derived Alkaloids

Abstract: Inhibition of the cardiac human ether-a-go-go-related gene channel is a problematic off-target pharmacological activity and, hence, a major safety liability in clinical practice. Several non-cardiac drugs have been restricted in their use, or even removed from the market due to this potentially fatal adverse effect. Comparatively little is known about the human ether-a-go-go-related gene inhibitory potential of plant-derived compounds. In the course of an ongoing human ether-a-go-go-related gene in vitro study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…1) isolated from Macleaya cordata [25], two protoberberines corypalmine (IC 50 value 128.0 ± 10.5 μM; Fig. 1) and canadine (IC 50 value 152.0 ± 12.5 μM) from Corydalis cava [26], and finally by the aporphine type alkaloid N-methyllaurotetanine (IC 50 value 135.0 ± 11.7 μM) from Eschscholtzia californica [17].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1) isolated from Macleaya cordata [25], two protoberberines corypalmine (IC 50 value 128.0 ± 10.5 μM; Fig. 1) and canadine (IC 50 value 152.0 ± 12.5 μM) from Corydalis cava [26], and finally by the aporphine type alkaloid N-methyllaurotetanine (IC 50 value 135.0 ± 11.7 μM) from Eschscholtzia californica [17].…”
Section: Resultsmentioning
confidence: 99%
“…[26]. Dihydrosanguinarine was isolated from a commercial extract of Macleaya cordata [25]. (-)-Platycerine was isolated from aerial parts of Argemone platyceras.…”
Section: Resultsmentioning
confidence: 99%
“…Our results highlight the safety concerns regarding the internal use of C. majus: orally applied greater celandine products need cautious evaluation from the view of both hepatic and cardiovascular side effects. With regard to similar hERG blocking activity of related natural alkaloids [11], further studies are warranted to evaluate potential hERG-related safety aspects of medicinal plant extracts and to assess the clinical relevance of these findings.…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies have demonstrated that berberine [6][7][8][9], chelerythrine [10], chelidonine [11], sanguinarine [11], and protopine [11] have hERG ion channel activities. The human ether-à-go-go-related gene (hERG, KCNH2, Kv11.1) encodes a cardiac voltage-gated potassium channel that provides the major repolarizing current (rapidly activating delayed rectifier potassium current, I Kr ) in phase 3 of the cardiac action potential.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation